2013
DOI: 10.1016/j.clim.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cytokine therapies in T1D: Concepts and strategies

Abstract: Therapeutic targeting of proinflammatory cytokines is clinically beneficial in several autoimmune disorders. Several of these cytokines are directly implicated in the pathogenesis of type 1 diabetes, suggesting opportunities for design of clinical trials in type 1 diabetes that incorporate selective cytokine blockade as a component of preventative or interventional immunotherapy. The rationale and status of inhibitory therapy directed against IL-1, TNF, IL-12, IL-23, and IL-6 are discussed, towards a goal of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 59 publications
(61 reference statements)
1
43
0
1
Order By: Relevance
“…The proinflammatory cytokine TNF-a, expressed in the infiltrating immune cells, is known to be a key player in the pathology of many autoimmune diseases, including T1D (9,12,13). However, although a monotherapy with anti-TNF-a is an established successful therapy in a number of autoimmune diseases (15)(16)(17), anti-TNF-a is not effective in T1D treatment (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proinflammatory cytokine TNF-a, expressed in the infiltrating immune cells, is known to be a key player in the pathology of many autoimmune diseases, including T1D (9,12,13). However, although a monotherapy with anti-TNF-a is an established successful therapy in a number of autoimmune diseases (15)(16)(17), anti-TNF-a is not effective in T1D treatment (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidence from studies in a variety of other autoimmune diseases supports the contention that the inflammatory process in the affected organs always goes along with a high TNF-a expression (9)(10)(11)(12)(13). Anti-TNF-a therapy is therefore an established therapeutic principle (14)(15)(16) in rheumatoid arthritis, inflammatory bowel diseases, lupus erythematosus, Sjögren syndrome, psoriasis, and Hashimoto thyroiditis (10,15,17).…”
mentioning
confidence: 99%
“…At the onset of T1D, the inflammatory response is thought to be directed toward pancreatic islets (2), a process that seems to play a crucial role in maintaining the autoimmune response as well as representing a key feature of its pathology (3). Consequently, control of the inflammatory response is a strategic and somewhat underexplored action for influencing the disease (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Administration of ponesimod to diabetic NOD mice followed by anti-CD3 mAb treatment, started a few days before discontinuation of ponesimod, induced long-lasting disease remission in all treated mice [130]. IL-1β is an interesting therapeutical target in T1D as it has been shown to inhibit insulin secretion and synthesis and to affect β-cell viability [131]. Ablamunits et al found synergistic reversal of autoimmune diabetes and enhanced immune regulation in NOD mice treated with anti-CD3 mAb together with IL-1 receptor antagonist [132].…”
Section: Review Kuhn and Weinermentioning
confidence: 98%